The Mechanical Performance of Re-Bonded and Healed Adhesive Joints Activable through Induction Heating Systems - Raffaele Ciardiello (MDPI AG, 2021)
This work aims to study the healing potential properties of a reversible thermoplastic adhesive. The adhesive is activable by using induction heating systems that can induce thermal heat in the particles throughout the electromagnetic field so they can melt the adhesive for bonding or separation procedures. The healing procedure consists of damaging single lap joint (SLJ) specimens with quasi-static and fatigue tests and then using an inductor to generate an electromagnetic field able to heat the adhesive to its melting point in order to heal the damaged SLJ specimens. SLJ tests were performed on damaged and healed specimens to assess, respectively, the residual mechanical properties of the damaged specimens and the mechanical properties after healing. SLJ tests showed that the healing procedure can completely recover the joint stiffness of the damaged adhesive joints, a huge part of the maximum shear strength and the SLJ absorbed energy. This work shows also the possibility of re-bonding completely failed or separated SLJs by using the same procedure. The mechanical properties of SLJs after healing and re-bonding are compared to the SLJ compared on virgin specimens to assess the recovered mechanical properties.